2015
DOI: 10.1371/journal.pone.0122056
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Control of Sporadic Proliferation in Growth Arrested Swiss 3T3 Feeder Cells

Abstract: Growth arrested Swiss mouse embryonic 3T3 cells are used as feeders to support the growth of epidermal keratinocytes and several other target cells. The 3T3 cells have been extensively subcultured owing to their popularity and wide distribution in the world and, as a consequence selective inclusion of variants is a strong possibility in them. Inadvertently selected variants expressing innate resistance to mitomycin C may continue to proliferate even after treatment with such growth arresting agents. The failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Recent work has demonstrated a risk of sporadic proliferation in growth‐arrested J2 3T3 feeder cells due to development of resistance to the MC drug (Chugh, Chaturvedi, & Yerneni, ). In this study, we found presence of feeder layer cells in four out of six cultures (sample donors #M1, M3, M4, and M6) after Passage 2, which was therefore identified as contamination of still proliferating J2 3T3 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has demonstrated a risk of sporadic proliferation in growth‐arrested J2 3T3 feeder cells due to development of resistance to the MC drug (Chugh, Chaturvedi, & Yerneni, ). In this study, we found presence of feeder layer cells in four out of six cultures (sample donors #M1, M3, M4, and M6) after Passage 2, which was therefore identified as contamination of still proliferating J2 3T3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found presence of feeder layer cells in four out of six cultures (sample donors #M1, M3, M4, and M6) after Passage 2, which was therefore identified as contamination of still proliferating J2 3T3 cells. This problem could be avoided by employing culture and subculture protocols that identify and control the proliferation of this cell line (Chugh et al, ; Chugh, Chaturvedi, & Yerneni, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these feeder cells provided a qualified environment in co‐culture with a variety of cell types, through intermediating different mechanisms including cell‐cell and cell‐extracellular matrix interactions, secretion of soluble growth factors as well as removing toxicants from culture medium . Latest study suggest that using mouse embryonic 3T3 feeder layer can greatly increase the number of stem cells and it is useful in supporting and maintenance of the target cells . However, the mouse feeder cells contains N‐glycolylneuraminic acid and non‐human sialic acid (Neu5Gc), an immune response could be induced when we use the cells for transplantation, since most people have Neu5Gc circulating antibodies…”
Section: Introductionmentioning
confidence: 99%
“…In practical terms, such permutations represent a range of volumes of treating MC solutions which are directly and indirectly proportional to the derived dose per cell and concentration per se, respectively. Because, the 3T3 cultures were known to gradually accumulate spontaneous variants with altered characteristics (Rubin and Xu 1989;Matthews 1993), the exposure cell number has to be set to such a constant level that the cell population does not accumulate MC-resistant variants through successive passaging (Chugh et al 2015a). Accordingly, the titration of a safe density of feeder cells with varied volumes of a MC solution of a less toxic but effective concentration would then enable identification of a specific concentration-dose permutation that produced ideal feeder cell extinction which in turn influenced optimal stem cell proliferation.…”
mentioning
confidence: 99%